Biofilm formation on a TiO2 nanotube with controlled pore diameter and surface wettability. (20th January 2015) - Anitha, V C; Lee, Jin-Hyung; Lee, Jintae; Narayan Banerjee, Arghya; Woo Joo, Sang; Ki Min, Bong
Abstract: Titania (TiO2 ) nanotube arrays (TNAs) with different pore diameters (140 − 20 nm) are fabricated via anodization using hydrofluoric acid (HF) containing ethylene glycol (EG) by changing the HF-to-EG volume ratio and the anodization voltage. To evaluate the effects of different pore diameters of TiO2 nanotubes on bacterial biofilm formation, Shewanella oneidensis (S. oneidensis) MR-1 cells and a crystal-violet biofilm assay are used. The surface roughness and wettability of the TNA surfaces as a function of pore diameter, measured via the contact angle and AFM techniques, are correlated with the controlled biofilm formation. Biofilm formation increases with the decreasing nanotube pore diameter, and a 20 nm TiO2 nanotube shows the maximum biofilm formation. The measurements revealed that 20 nm surfaces have the least hydrophilicity with the highest surface roughness of ∼17 nm and that they show almost a 90% increase in the effective surface area relative to the 140 nm TNAs, which stimulate the cells more effectively to produce the pili to attach to the surface for more biofilm formation. The results demonstrate that bacterial cell adhesion (and hence, biofilm formation) can effectively be controlled by tuning the roughness and wettability of TNAs via controlling the pore diameters of TNA surfaces. This biofilm formation as a function of the surface properties of TNAs can be a potential candidate for both medical applications and as electrodes in microbial fuel cells.